Revisiting the impacts of green purchasing practices on environmental and economic performances: A case study for the Marmara region of Türkiye - Ali Ibrahim Balin; Billur Engin Balin (Sustainable Futures)
The growing global emphasis on environmental sustainability and the role of businesses in addressing climate change has highlighted the importance of integrating green purchasing practices (GPPs) into supply chain management. This study investigates the impact of GPPs on environmental performance (EP) and economic performance (ECP) in companies operating within the Marmara Region of Türkiye, which contributes 35 % of the national GDP and houses over half of its manufacturing industry. Addressing a gap in existing literature, the study holistically evaluates four sub-activities of GPPs—supplier selection, supplier development, supplier collaboration, and supplier evaluation—and examines the mediating role of EP between GPPs and ECP. A survey was designed and conducted with 233 purchasing managers from small and medium enterprises (SMEs) and large enterprises in the region to achieve these aims. Exploratory and confirmatory factor analyses ensured the reliability and validity of constructs, while regression analysis tested hypotheses and mediating relationships. Results reveal that while GPPs significantly enhance both EP and ECP, not all sub-activities have uniform effects. Notably, EP partially mediates the relationship between GPPs and ECP, demonstrating that environmental improvements can offset initial costs and enhance financial outcomes. These findings provide a robust framework for addressing challenges in transitioning to GPPs in developing economies.